School Culture Program: Inculcating Anti- Corruption Values Through Honesty Canteen In State Elementary School: Case Study In Indramayu District, West Java, Indonesia - Rusydi, Ibnu (International Journal of Psychosocial Rehabilitation, 2020)
The article aims to describe concerning school culture program to inculcate anti corruption values within students in primarily school. To realize honesty values become community responsibility mainly the formal education in learning activities. The research conducted at State Elementary School in Indramayu District, West Java, Indonesia. The research was qualitative approach with case study. The data obtained through interview, observation, and documentation studies. The data were analyzed with Miles and Huberman with interactive models. The result sowed thatthe role of school culture was described in three main aspects, those are the perception of school atmosphere, the behavior of the student, and management of headmaster. The result of the study showed that honest. Honesty canteen in the school can help primary school students to actualize discipline, honesty, and integrity. The evaluation of honesty canteen is carried out by analyzing the financial report from the organizer and supervised by all school community..